2018
DOI: 10.1507/endocrj.ej17-0413
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of MIB-1 immunostaining for diagnosing hyalinizing trabecular tumour of the thyroid: semi-automated techniques with manual antigen retrieval are more accurate than fully automated techniques

Abstract: Abstract. Hyalinizing trabecular tumour (HTT) immunohistochemically shows cell membranous immunoreactivity for MIB-1. This aberrant immunoreactivity is an important factor for the diagnosis of HTT. However, fully automated stainers frequently fail to confirm the immunoreactivity. The aim of this study is to investigate the cause of false negative cell membranous immunoreactivity for MIB-1 in HTT using fully automated stainers, to determine potential reasons for the problem, and to establish methods confirming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Immunohistochemistry can assist in diagnosing HTT, even though some of the biomarkers employed may not show significant specificity . In keeping with the follicular cell origin of HTT, different authors, including our group, have used HBME‐1 and galectin‐3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry can assist in diagnosing HTT, even though some of the biomarkers employed may not show significant specificity . In keeping with the follicular cell origin of HTT, different authors, including our group, have used HBME‐1 and galectin‐3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not used in our study, mostly due to the difficulties in recognizing the cytological features of HTT, numerous papers have concluded that MIB‐1 is also a useful diagnostic tool in cytological samples . HTT shows a distinctive membrane and cytoplasmic positivity for Ki‐67 (using the clone MIB‐1) when the reaction is performed at room temperature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTT does not show BRAF (V600E) mutation [ 9 ]. HTT has a unique immunohistochemical staining pattern for Ki-67 MIB1 monoclonal antibody, which is positive in peripheral tumor cell cytoplasm but expressed in the nuclei of most other tumors [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, immunohistochemistry and mutation tests are difficult to perform on cytology specimen and are not sufficient to rule out PTC and diagnose HTT on FNA. General use of Ki-67 staining in HTT FNA specimens is also expensive; therefore, Ki-67 staining should be limited to carefully selected inconclusive cases, for example those cases showing nuclear features of PTC but with sparse hyaline material [ 2 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%